INTEGRASI LEVEL OF SERVICE (LOS) DAN KEPADATAN UMKM SEBAGAI DASAR PENETAPAN PRIORITAS PENINGKATAN JARINGAN JALAN DI KOTA CIREBON - Khairi Ahza Hail Keliwar; Ummu Kultsum Muhammad; Fathiyah Rahmi Hidayat (STKIP PGRI Situbondo, 2026)
The City of Cirebon is part of the Rebana Metropolitan Area and possesses significant potential in the MSME sector. Economic growth and increasing population mobility require a reliable and efficient transportation system. However, persistent transportation problems such as traffic congestion can reduce community income and hinder the distribution system of goods and services. This study aims to assess the Level of Service (LoS) of road segments in the City of Cirebon as a basis for determining priority road network improvements to support MSME development. The analytical methods employed include LoS analysis calculated in accordance with the PKJI 2023 and visualized using ArcGIS. MSME density was analyzed using KDE in ArcGIS. Furthermore, spatial overlay analysis was applied to integrate the LoS results with MSME density patterns. The findings indicate that the LoS values of the 19 observed road segments in the City of Cirebon vary considerably. Approximately 47.37% of the segments fall within LoS D-F, indicating traffic conditions ranging from approaching unstable flow to severe congestion at LoS F, where maximum vehicle speeds are limited to approximately 15 km/h. The KDE analysis reveals that the highest concentration of MSMEs is predominantly located in Kejaksan and Pekalipan Districts. Meanwhile, the spatial overlay analysis identifies priority road segments that require immediate attention to support MSME activities in the City of Cirebon, namely Wahidin Sudirohusodo Street and Sunan Gunung Jati Street in Kejaksan District, as well as Pekalipan Street and Nyi Mas Gandasari Street in Pekalipan District.